Zirconium hydrazinediido complexes derived from cyclic hydrazines and their role in the catalytic synthesis of 1,7-annulated indoles - Scholl, Solveig A.; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2013)
Reaction of cyclic 1,1′-disubstituted hydrazines with the bis(dimethylamido)zirconium complex [Zr{(NXyl)2Npy} (NMe2)2] (1) in the presence of dmap yielded the hexacoordinate zirconium hydrazinediido complexes [Zr{(NXyl)2Npy}(═NNC9H10)(dmap)2] (2) and [Zr{(NXyl)2Npy}(═NNC12H8)(dmap)2] (3). Hydrazinediides are thought to be key intermediates in the zirconium-catalyzed reaction of cyclic 1,1′-disubstituted hydrazines and disubstituted alkynes to yield 1,7-annulated indoles. Their basic structural motif is found in 5-HT3 receptor antagonists such as Cilansetron.
Gesehen am 15.07.2021